Mengapa Masyarakat Indonesia Terus Menggunakan Layanan Mobile Payment? - Gaffar, Mohammad Rizal; Sutisna, Mamun; Senalasari, Widi (Universitas Nusa Putra, 2020)
In Indonesia by 2007, Telkomsel launched TCash as the pioneer of mobile payment service provider. In the next year Indosat launched Dompetku and XL also offered the same service which is XL Tunai in 2012. The interesting part start when GoPay as the newcomer in mobile payment services had the same number of users with TCash. The great market value and the large number of players in the mobile payment business require service providers to understand and capture what consumers really need. Therefore, a model is developed which can represent post-consumer behavior using mobile payment services. This research used a set of questionnaire and valid data gathered from 200 samples from Bandung, Indonesia. We analyzed the data by Partial Least Square. The result shows that the model has a strong predictive power for measuring consumer behavior towards the use of mobile payment and all the hypotheses were accepted.